2014
DOI: 10.4103/0973-6131.123486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga on the Myofascial Pain Syndrome of neck

Abstract: Myofascial Pain Syndrome (MPS) refers to pain attributed to muscle and its surrounding fascia, which is associated with “myofascial trigger points” (MTrPs). MTrPs in the trapezius has been proposed as the main cause of temporal and cervicogenic headache and neck pain. Literature shows that the prevalence of various musculoskeletal disorders (MSD) among physiotherapists is high. Yoga has traditionally been used to treat MSDs in various populations. But there is scarcity of literature which explains the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…Pain levels decreased similarly to the control group (C) but only on two pain categories of the NPRS (present and worst pain intensity), while not observing any statistically significant difference in pain levels of the category of NPRS “pain at best” before and after treatment. More generally, therapeutic training groups B and C, which aimed to exercise the neck superficial muscles of the cervical spine lasting 7 weeks, showed that Groups B and C were able to reduce pain levels, a fact confirmed by the very recent literature [28, 29]. …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Pain levels decreased similarly to the control group (C) but only on two pain categories of the NPRS (present and worst pain intensity), while not observing any statistically significant difference in pain levels of the category of NPRS “pain at best” before and after treatment. More generally, therapeutic training groups B and C, which aimed to exercise the neck superficial muscles of the cervical spine lasting 7 weeks, showed that Groups B and C were able to reduce pain levels, a fact confirmed by the very recent literature [28, 29]. …”
Section: Discussionsupporting
confidence: 56%
“…Generally, the majority of previous research studies found that the PPT levels on the cervical extensor muscles are not affected by the application activity in these muscles [3032]. In contrast, the study of Sharan et al [29], a sample of eight people (physiotherapists), showed great differences (statistically significant) between the initial and final measurements of PPT levels after applying yoga-term program 4 weeks. However, the absence of a control group and insufficient explanation and presentation reliability of the material and the methodology used by Sharan et al [29] and the omission of the cervical muscles in which the PPT were measured make the study vulnerable to potential biases.…”
Section: Discussionmentioning
confidence: 96%
“…Yoga therapy for 5 times, 4 weeks a week, significantly improved VAS score in patients with myofascial pain syndrome. [24] Practicing yoga asana for 4 weeks led to significant reduction of VAS scores in chronic low back pain patients. [25] Moreover, yoga training reduced the intensity and frequency of headaches in patients suffering from migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Despite yoga being an integral part of Indian culture, clinical research into using yoga as treatment modality has been initiated only in the last few decades. Findings in recent studies have been encouraging for using yogabased interventions in pain disorders (Bower, Garet, & Sternlieb, 2011;Carson, Carson, Jones, Bennett, Wright, & Mist, 2010;Cramer, Lauche, Langhorst, Dobos, & Michalsen 2014;Do Ros ario, Orcesi, Kobayashi, Aun, & Diolindo Assumpção, 2013;Lee, Moon, & Kim, 2014;Nambi, Inbasekaran, Khuman, Devi, & Shanmugananth, 2014;Rudrud, 2012;Sharan, Manjula, Urmi, & Ajeesh, 2014). Studies have demonstrated therapeutic effects of yoga in chronic pain conditions such as low back ache, headache, fibromyalgia, and chronic fatigue syndrome (Bhatia, Dureja, Tripathi, Bhattacharjee, Bijlani, & Mathur, 2007;Holtzman & Beggs, 2013;Lauche, Cramer, H€ auser, Dobos, & Langhorst, 2015;Oka, Tanahashi, Chijiwa, Lkhagvasuren, Sudo, & Oka, 2014).…”
Section: Introductionmentioning
confidence: 93%